Efeito do tipo de explante e reguladores de crescimento vegetal na indução de calos em três cultivares de Psidium guajava visando a produção de metabólitos secundários - Scotá, Mayla Bessa (2023)
Psidium guajava (guava) is known for the commercialization of fruits for ornamental and medicinal purposes, using infusions of leaves and roots, where the presence of secondary metabolites (MeS) that are beneficial to health is observed. Infusion of leaves, roots or even the bark of the species P. guajava is widely used to treat gastrointestinal diseases such as stomach pain, dysentery and constipation. Biotechnological approaches such as plant tissue culture (CTV) techniques, such as biomass production through callogenesis, are used to provide plant material on a large scale in a standardized way and can be used to supply and mitigate the overexploitation of medicinal plants taken from native sources or cultivated areas. The general objective of this work was to induce callogenesis in vitro using different combinations of plant growth regulators (PGRs) (2,4-D, ANA, KIN and BAP) and explants of leaves, hypocotyls and roots, extracted from P. guajava germinated in vitro from the cultivars Paluma and Cortibel (C1 and C6). For this, the parameters of IVG and % of germination were evaluated; callus induction on leaf, hypocotyl and root explants; anatomical evaluation of in vitro calluses from leaf explants of the Paluma cultivar from 0 to 49 days of incubation; phytochemical prospection in aqueous and alcoholic extract of callus biomass from leaf explants of Paluma and Cortibel cultivars (C1 and C6) cultivated under the influence of the combination of PGRs 2.0 mg L-1 2.4-D + 1.0 mg L-1 ANA + 1.0 mg L-1 KIN (T1), which showed the best callus induction averages in the three cultivars tested in order to identify the presence of MeS synthesized from the callus tissue biomass. The combination of PGRs 2.0 mg L-1 2,4-D + 1.0 mg L-1 ANA + 1.0 mg L-1 KIN (T1), at 60 days, promoted 100% callus induction in leaf explants of the tested cultivars, and greater than 85% in the other combinations of PGRs tested in Paluma and Cortibel (C1 and C6). Important MeS groups were detected, such as tannins, flavones, saponins, chalcones and aurones by phytochemical prospecting in Paluma and Cortibel cultivars (C1 and C6), and the catechins group only in Cortibel (C1 and C6). Leaf explants were more susceptible to callogenesis in vitro in a shorter time than hypocotyl and root explants in the tested cultivars, Paluma and Cortibel (C1 and C6), and, ability to synthesize MeS, being, therefore, recommended for obtaining greater amount of plant biomass.